2015
DOI: 10.1038/ncomms10232
|View full text |Cite
|
Sign up to set email alerts
|

Draxin from neocortical neurons controls the guidance of thalamocortical projections into the neocortex

Abstract: The thalamocortical tract carries sensory information to the neocortex. It has long been recognized that the neocortical pioneer axons of subplate neurons are essential for thalamocortical development. Herein we report that an axon guidance cue, draxin, is expressed in early-born neocortical neurons, including subplate neurons, and is necessary for thalamocortical development. In draxin−/− mice, thalamocortical axons do not enter the neocortex. This phenotype is sufficiently rescued by the transgenic expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 68 publications
3
38
0
Order By: Relevance
“…However, this is not expected as very few new guidance cues have been discovered over the last decade or so. Draxin, a secreted protein that has no homology with other previously identified guidance cues, was identified as a repellent for axons in the developing brain and spinal cord (Islam et al, 2009;Shinmyo et al, 2015;Ahmed et al, 2011), and a guidance function was recently demonstrated for phosphatidyl-β-D-glucoside and its derivative lyso-phosphatidyl-β-D-glucoside (LysoPtdGlc) expressed on glial cells in the dorsal spinal cord (Guy et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, this is not expected as very few new guidance cues have been discovered over the last decade or so. Draxin, a secreted protein that has no homology with other previously identified guidance cues, was identified as a repellent for axons in the developing brain and spinal cord (Islam et al, 2009;Shinmyo et al, 2015;Ahmed et al, 2011), and a guidance function was recently demonstrated for phosphatidyl-β-D-glucoside and its derivative lyso-phosphatidyl-β-D-glucoside (LysoPtdGlc) expressed on glial cells in the dorsal spinal cord (Guy et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A single gene was located within the BTA9 selection peak—the phosphodiesterase 7B gene ( PDE7B ), which has been associated with neurobiological processes (de Gortari and Mengod, 2010) and has been previously linked to genetic changes associated with dog ( Canis lupus familiaris ) domestication and behaviour (Freedman et al, 2016). A single gene was also located within the BTA16 selection peak—the dorsal inhibitory axon guidance protein gene ( DRAXIN ), which encodes a protein that regulates axon guidance, neural circuit formation and vertebrate brain development (Islam et al, 2009; Shinmyo et al, 2015). Twenty-four genes were located within the BTA17 selection peak, including BICDL1 , RAB35 and RNF10 , which have been associated with neurobiology and brain development (Hoshikawa et al, 2008; Schlager et al, 2010; Villarroel-Campos et al, 2016) and SIRT4 and COQ5 that function in cellular metabolism (Kawamukai, 2015; Elkhwanky and Hakkola, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The protein promotes axon outgrowth when applied to dissociated thalamic neurons in a DCC and Neo1 dependent fashion. Additionally, compound mutants of Dcc and Neo1 show similar axonal phenotypes as Draxin null mutants in vivo (Shinmyo et al, ). This indicates that Dcc expressed by thalamic axons are important at several steps during the TCA pathfinding.…”
Section: Signaling Centers Patterning the Thalamusmentioning
confidence: 98%
“…The binding partner of Linx expressed on TCAs remains to be determined. Recently, Draxin expressed by cortical cells was shown necessary for TCAs to cross the PSB and enter into the cortex after passing the corridor (Shinmyo et al, ). The protein promotes axon outgrowth when applied to dissociated thalamic neurons in a DCC and Neo1 dependent fashion.…”
Section: Signaling Centers Patterning the Thalamusmentioning
confidence: 99%